Cultural interventions: Repositioning hip hop education in India - Singh, Jaspal Naveel; Dattatreyan, Ethiraj Gabriel (Linguistics and education, 2016)
•The state-sponsored internationalization of hip hop pedagogy entails processes of formalization, which can lead to contradictory perspectives and claims.•We employ sociolinguistic theorizations of scales to show up some of the contradictions that arise from north–south ‘development’ work.•Internationally-traveling hip hop pedagogues seem to negotiate the internationalization and formalization of hip hop by repositioning themselves as authentic.•In sociolinguistic terms, they rescale their arguments to index membership in both informal pedagogies of hip hop and formal pedagogies of the state.•Such insights can help hip hop pedagogues, ‘cultural’ organizations and policy-makers to develop a critical understanding of international pedagogy. In this article we show how subject positions are assumed when hip hop is used by institutions supported by western nation-states as a ‘cultural intervention’ in the global south. Focusing on the Indo-German Hip Hop & Urban Art Project 2011–2012, a hip hop educational project sited in several cities in India and sponsored by cultural institutions funded by the German State, we study how actors negotiate between what we identify as a discourse of hip hop authenticity and a discourse of internationalization. Employing a theory of scales allows us to investigate how actors on the ground engage in the semiotic play of repositioning of and in historically situated notions of authenticity and pedagogy. We argue that the findings have implications for future applied and theoretical work on the internationalization of hip hop as an educational and diplomatic endeavor.